Trapped in the Trenches: A World War One Story - Martin, Christopher (HarperCollins Publishers Ltd, 2002)
Soldiers in trenches in World War I were always close to death. Rats ran around their feet at night, gas attacks were a constant threat and you never knew if you'd be alive the next day. The only sure thing was that there was no way out$1! =s
Keywords: Juvenile Fiction / Historical-Worldwar I